Comparison of closed-cell and hybrid-cell stent designs in carotid artery stenting: clinical and procedural outcomes - TatlI, Ersan; Tokatli, Alptug; Vatan, Mehmet; Agac, Mustafa; Gunduz, Huseyin; Akdemir, Ramazan; Kilic, Harun (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction: Carotid artery stenting (CAS) is a promising alternative to surgery in high-risk patients. However, the impact of stent cell design on outcomes in CAS is a matter of continued debate. Aim : To compare the periprocedural and clinical outcomes of different stent designs for CAS with distal protection devices. Material and methods : All CAS procedures with both closed- and hybrid-cell stents performed at our institution between February 2010 and December 2015 were analyzed retrospectively. Adverse events were defined as death, major stroke, minor stroke, transient ischemic attack and myocardial infarction. Periprocedural and 30-day adverse events and internal carotid artery (ICA) vasospasm rates were compared between the closed-cell and hybrid-cell stent groups. Results : The study included 234 patients comprising 146 patients with a closed-cell stent (Xact stent, Abbott Vascular) (mean age: 68.5 ±8.6; 67.1% male) and 88 patients with a hybrid-cell stent (Cristallo Ideale, Medtronic) (mean age: 67.2 ±12.8; 68.2% male). There was no significant difference between the groups with respect to periprocedural or 30-day adverse event rates. While there was no difference in terms of tortuosity index between the groups, there was a higher procedural ICA vasospasm rate in the closed-cell stent group (35 patients, 23%) compared with the hybrid-cell stent group (10 patients, 11%) (p = 0.017). Conclusions : The results of this study showed no significant difference in the clinical adverse event rates after CAS between the closed-cell stent group and the hybrid-cell stent group. However, procedural ICA vasospasm was more common in the closed-cell stent group.